TINDAKAN KOMUNIKATIF PADA SISTEM BAHTSUL MATSAIL DI PONDOK PESANTREN AL AMIN; Musyawarah Kitab Kuning di Pondok Pesantren Putri Al Amin Ngasinan, Rejomulyo, Kota Kediri - Afia, Azkiyatul (Jurnal Sosiologi Reflektif, 2019)
The culture of interactive dialogue in seeking an agreement in determining shariâ€™a law that still requires detailed mediation in the public space referred to in Bahstul matsail. Scientific forums that are more familiar with this matter, are accommodated by the Al Amien Kediri Islamic Boarding School, where there are ulamaâ€™, religious teachers, and forum participants as a complement in determining a law that is still multi-interpretation. The agreement will be the basis of one law that is still biased, so that it indicates an agreement called Ijmaâ€™. The existence of mutualism symbiosis between the elements of Bahstul matsail is interesting in Habermasâ€™s study of public space in delivering ideas and opinions. Habermas in the public sphere sees that there is a dominance of communicative actions, one of them is social statification from Bahstul matsail participants in Habermas â€œbourgeois public spaceâ€ where the domination of scholarship in more to the ulama because it is considered more understandable about Shariâ€™a law.Budaya dialog interaktif dalam mencari sebuah kesepakatan dalam menetukan hukum syariat yang masih membutuhkan penjelasan secara rinci termediasi dalam ruang public yang di sebut dengan Bahtsul matsail. Forum ilmiah yang lebih akrab untuk hal ini, diwadahi oleh pondok pesantren Al-amin Kediri, dimana terdapat ulamaâ€™, ustadz dan peserta forum sebagai pelengkap dalam menentukan sebuah hukum yang masih multi tafsir. Kesepakatan akan menjadi dasar dari satu hukum yang masih bias, sehingga berindikasi kepada satu kesepakatan yang di sebut ijmaâ€™. Adanya symbiosis mutualisme antara elemen Bahtsul matsail menjadi menarik dalam kajian ruang public Habermas dalam penyampaian gagasan, ide dan pendapat. Habermas dalam ruang public melihat ada dominasi tindakan komunikatif salah satunya, statifikasi social dari peserta Bahsul matsail dalam Bahasa Habermas â€œRuang public borjuisâ€ dimana dominasi keilmuan lebih pada ulama lantaran dianggap lebih faham tentang hukum syariat.Â